2018
DOI: 10.1016/j.atherosclerosis.2018.06.814
|View full text |Cite
|
Sign up to set email alerts
|

Identification and diagnosis of patients with familial chylomicronaemia syndrome (FCS): Expert panel recommendations and proposal of an “FCS score”

Abstract: Familial chylomicronaemia syndrome (FCS) is a rare, inherited disorder characterised by impaired clearance of triglyceride (TG)-rich lipoproteins from plasma, leading to severe hypertriglyceridaemia (HTG) and a markedly increased risk of acute pancreatitis. It is due to the lack of lipoprotein lipase (LPL) function, resulting from recessive loss of function mutations in the genes coding LPL or its modulators. A large overlap in the phenotype between FCS and multifactorial chylomicronaemia syndrome (MCS) contri… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
108
0
46

Year Published

2019
2019
2024
2024

Publication Types

Select...
4
2

Relationship

1
5

Authors

Journals

citations
Cited by 154 publications
(156 citation statements)
references
References 52 publications
2
108
0
46
Order By: Relevance
“…Indeed, it has been recently shown that fasting triglyceride levels >10 mmol/L (885 mg/dL) on multiple occasions, refractory to standard triglyceride-lowering therapies, a young age at onset, the lack of secondary factors, and a history of episodes of AP are powerful predictors of FCS. 3 In agreement with previous reports, 6 the most common molecular defect in FCS patients was represented by rare loss-of-function mutations in LPL gene. We detected 9 LPL mutations, 3 of which are already known to be causative of FCS 26 (https://www.omim.org/ entry/609708), whereas 4 were novel and 2 known but never associated to FCS phenotype.…”
Section: Discussionsupporting
confidence: 90%
See 4 more Smart Citations
“…Indeed, it has been recently shown that fasting triglyceride levels >10 mmol/L (885 mg/dL) on multiple occasions, refractory to standard triglyceride-lowering therapies, a young age at onset, the lack of secondary factors, and a history of episodes of AP are powerful predictors of FCS. 3 In agreement with previous reports, 6 the most common molecular defect in FCS patients was represented by rare loss-of-function mutations in LPL gene. We detected 9 LPL mutations, 3 of which are already known to be causative of FCS 26 (https://www.omim.org/ entry/609708), whereas 4 were novel and 2 known but never associated to FCS phenotype.…”
Section: Discussionsupporting
confidence: 90%
“…Overall, these findings are consistent with the emerging model indicating that severe hypertriglyceridemia phenotype may be caused by the contribution of multiple alleles with large or minor effects interacting each others. 3 However, a clear explanation of mechanisms linking the increased burden of small-effect variants in triglyceride genes with the extreme elevation of plasma triglycerides is not available. Previous observations have highlighted the importance of alterations in the kinetic of LPL activation.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations